Adapting to the new sporting goods market era: Adidas differentiation in digital retail - Barbosa, Duarte Latino Tavares (2022)
The following Equity Research accesses Adidas AG, the largest sportswear company in Europe. The analysis explores the arguments for a BUY recommendation that resulted from a Discounted Cash Flow valuation with a target price of €275.1. To forecast Adidas AG's Free Cash Flows, the firm's historical performance, as well as industry trends, opportunities, and risks, were thoroughly analyzed. The paper places special emphasis on the company’s future value drivers in a post-pandemic scenario. With the sporting goods market having a strong recovery and a major shift to digital sales and marketing. The capacity to connect with consumers in the digital world and seize growth in the Women's and Sustainability segments, andGreater China region, will determine success in this industry.